2021
DOI: 10.1051/cagri/2021005
|View full text |Cite
|
Sign up to set email alerts
|

Performance économique des chaînes de valeur des crevettes d’eaux douces au Bénin

Abstract: L’exportation des crevettes du Bénin pourrait se développer, mais reste quasi-inexistante en raison du non-respect des normes sanitaires exigées sur le marché international, ce qui fragilise la durabilité des chaînes de valeur de crevettes. Cette étude évalue les performances économiques des chaînes de valeur de crevettes d’eaux douces au Bénin. Les approches conceptuelle et comptable de la chaîne de valeur ont été utilisées pour identifier les acteurs, analyser les liens d’affaires et évaluer le processus de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Macrobrachium species are the most fished and traded among the exploited freshwater prawns’ species and constitute an important source of income and animal protein for local people (Houngbo et al., 2015; Ollabodé, 2019). Among these species, Macrobrachium macrobrachion , beside Macrobrachium vollenhoveni , is one of the two species most appreciated by Beninese consumers and economically important in terms of subsistence fishing (Koussovi et al., 2020; Ollabodé, 2019). Therefore, it is exploited intensively in all fisheries by artisanal fisherman for their subsistence or trade (Houngbo et al., 2015; Koussovi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Macrobrachium species are the most fished and traded among the exploited freshwater prawns’ species and constitute an important source of income and animal protein for local people (Houngbo et al., 2015; Ollabodé, 2019). Among these species, Macrobrachium macrobrachion , beside Macrobrachium vollenhoveni , is one of the two species most appreciated by Beninese consumers and economically important in terms of subsistence fishing (Koussovi et al., 2020; Ollabodé, 2019). Therefore, it is exploited intensively in all fisheries by artisanal fisherman for their subsistence or trade (Houngbo et al., 2015; Koussovi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is predominantly consumed as a food and condiment in many African countries, especially in rural areas. In Benin, M. macrobrachion is exploited and sold in three forms as fresh, smoked, and fried prawns and, therefore, are more profitable and provide an economic benefit (Ollabodé et al, 2021). It contributes 67.2% to the value chains (Houngbo et al, 2015; Ollabodé et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Benin, M. macrobrachion is exploited and sold in three forms as fresh, smoked, and fried prawns and, therefore, are more profitable and provide an economic benefit (Ollabodé et al, 2021). It contributes 67.2% to the value chains (Houngbo et al, 2015; Ollabodé et al, 2021). According to Koussovi et al (2019), this species is a suitable candidate for the development of native freshwater prawn aquaculture in Benin to meet demand from local and international consumers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, statistical data clearly show that the quantity of shrimps exported from Benin has dropped from 630 tons in 2002 to 1.5 tons in 2009 [29]. Recent investigations have shown that shrimp exports from Benin remain almost non-existent due to poor sheries management [4,38,47]. For the moment, the real causes of this decline are not well understood.…”
mentioning
confidence: 99%